Seeing The Meaning Of Cost In The Ngurisan Tradition On Lombok Island - Nina Fitriani,; Rini Ridhawati, (International Economic Conference of Business and Accounting, 2025)
This study examines the meaning of costs in the Ngurisan tradition for Sasak people on Lombok Island and compares it with an accounting perspective. Using qualitative research methods with an ethnographic approach, this research explores the community's understanding of accounting practices, especially in viewing costs in the Ngurisan tradition process. Ethnography was chosen to understand the meaning of costs from a cultural perspective through the experiences of individuals and groups involved in the Ngurisan tradition. The result of this study shows that the costs incurred for this tradition are different from the matching concept from the accounting perspective. The Sasak people interpret the cost incurred in this tradition as a necessity to carry out traditions that have been passed down for a long time, as well as a form of gratitude for being given a healthy child. Thus, the costs incurred do not aim to earn income as in the matching concept in conventional accounting. For the Sasak people, the return from the costs incurred in the Ngurisan tradition is not material but spiritual satisfaction and pleasure.